2008
DOI: 10.1007/s10620-008-0649-4
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of EphA2 and EphrinA-1 in Human Gastric Adenocarcinoma and Its Prognostic Value for Postoperative Patients

Abstract: This study aims to investigate the expression and significance of EphA2 and EphrinA-1 in human gastric adenocarcinoma progression and prognosis. The expression of EphA2 and EphrinA-1 was detected in the cell lines and tissues of gastric adenocarcinoma. Different expression levels of EphA2 and EphrinA-1 were found in two cell lines. The expression of EphA2 and EphrinA-1 was significantly higher in gastric adenocarcinoma tissues than in normal tissues. Statistical analysis showed a significant correlation of Eph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 21 publications
5
48
0
Order By: Relevance
“…However, the underlying mechanisms for the high expression of EphA2 protein in tumor remain incompletely understood but likely involve both transcriptional and posttranscriptional mechanisms. Our data that both mRNA and protein expression of EphA2 were elevated in SCCHN tissue samples and similar Wndings in gastric carcinoma (Yuan et al 2009) indicated the pre-transcriptional mechanism in SCCHN. However, other studies hypothesized that the unstable cell to cell contacts in malignant cells could functionally decrease EphA2 binding possibility with its membrane-anchored ligands, further preventing ligand-mediated degradation, which contributes to the high expression of EphA2 in tumor cells (WalkerDaniels et al 2002;Kikawa et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…However, the underlying mechanisms for the high expression of EphA2 protein in tumor remain incompletely understood but likely involve both transcriptional and posttranscriptional mechanisms. Our data that both mRNA and protein expression of EphA2 were elevated in SCCHN tissue samples and similar Wndings in gastric carcinoma (Yuan et al 2009) indicated the pre-transcriptional mechanism in SCCHN. However, other studies hypothesized that the unstable cell to cell contacts in malignant cells could functionally decrease EphA2 binding possibility with its membrane-anchored ligands, further preventing ligand-mediated degradation, which contributes to the high expression of EphA2 in tumor cells (WalkerDaniels et al 2002;Kikawa et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…26,27 High levels of EphA2 were also found in breast cancer, 28,29 prostate cancer, 30 lung cancer, 31 malignant glioma 32 and gastric cancer. 33 Although the EphA2/ephrinA1 pathway can be linked to tumor neovascularization 34 and the formation of tubular structures in metastatic melanoma, 35 most data reveal its role in cell proliferation and modulation of the cytoskeleton. Activation of EphA2 receptor negatively regulates the growth and survival of different tumor cell models.…”
Section: Do Not Distributementioning
confidence: 99%
“…We used score 3 as a cut off value above which was considered as over expression and below which was considered as low expression [9].…”
Section: Evaluation Of Immunohistochemical Expression Of Epha2mentioning
confidence: 99%
“…Studies addressing the association between HER2-neu expression and GAC patient's prognosis were conflicting as some studies demonstrated positive correlation between HER2-neu expression and GAC patient's prognosis while other studies failed to demonstrate similar results [6][7][8]. Erythropoietin-producing hepatocellular (Eph) molecules are major detected RTKs members that is detected at lower levels in non-neoplastic-epithelial cells [9], and it has many different functions in cancers as tumor initiation, progression, angiogenesis and spread [10,11]. EphA2 receptor is a RTK-Ras signaling component [12].…”
Section: Introductionmentioning
confidence: 99%